SYNTHESIS OF POLY (OCTANEDIOL CITRATE) BASED NANO SILICA COMPOSITE FOR BIOMEDICAL APPLICATION - MAHMUD, ABDULLAHI (2021)
Synthetic polymers are currently being used for biomedical applications, and citric acid has been used to develop novel polymers. However, the biomaterials presently available are of limited versatility for biomedical applications, and additional biodegradable polymer composite product would hence be beneficial to the biomedical field. Therefore, this research aimed at developing a biocompatible citric acid based polymer composite for biomedical applications. In this research, poly (octanediol citrate) (POC) synthesised through a polycondensation method was used to develop a polymer composite by mixing with nano silica synthesised from rice husk HCl acid pretreatment and calcination, to enhance biomaterial strength and biocompatibility. Five different composite formulations were made by adding (20 - 60wt.%) nano silica into the POC prepolymer to fabricate a strong, biocompatible composite via the thermo-cure casting technique.